IMPROVING METHODS OF TEACHING THE RUSSIAN LANGUAGE FOR ENGINEERING AREAS (Journal of Universal Science Research, 2023)
This scientific article investigates the challenges and opportunities in teaching the Russian language to students pursuing engineering fields. As engineering programs have become increasingly international, students are often required to learn specialized technical vocabulary and communicate effectively in Russian. The article explores innovative teaching methods, strategies, and technologies that can enhance the language learning experience for engineering students. By addressing the specific needs of this student population, institutions can better prepare their students for success in a globalized engineering landscape.